Eksistensi Pasar Tradisional Beringharjo terhadap Perkembangan Pariwisata Yogyakarta - Pramadana Noble, Ignatius Jovadondi; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p25, 2021)
The study aims to the growing tourism sector in Yogyakarta, Beringharjo Traditional Market does not want to be outdone to become a shopping tourist destination for tourists who come to Yogyakarta. With the many modern markets, the Beringharjo Traditional Market still exists among tourists. This study aims to find out how the existence of the Beringharjo Traditional Market according to the perceptions of traders and tourists and the manager's role. This study uses primary and secondary data sources. The type of data used is qualitative and quantitative data. Methods of collecting data through observation, interviews, documentation, and literature studies. Determination of informants in this study using purposive sampling technique. The data analysis used is descriptive qualitative. The results of this study indicate that the existing conditions are described by the 4A concept in the form of attractions include shopping and culinary tours, accesibility includes The Transjogja public transportation, the aminities include parking area, market radios, videotrone market areas, market security voices, loading and unloading facilities, clean toilets, trash cans, escalators connecting upstairs, prayer rooms, health clinics, relaxing lactation facilities, electronic retribution systems, cooperative services and banking, and child care, ancillary at Beringharjo Traditional market managed by the Industry and trade officetourist arrivals in the Beringharjo Traditional Market are increasing from year to year so that the income earned by traders is also increasing. The facilities provided by the manager are also getting better including garbage bins, toilets, CCTV, and other Keywords : The Existence, Beringharjo Traditional Market, Yogyakarta